Zinc complex crystal material for fluorescence detection of metal ions as well as preparation method and application of zinc complex crystal material

By synthesizing a zinc complex crystal material, the fluorescence emission performance is used to achieve rapid detection of iron, chromium and aluminum ions in water, solving the problem of insufficient detection speed and efficiency in the prior art, and achieving high sensitivity and selective response to these metal ions.

CN119875134AActive Publication Date: 2025-04-25NINGBO UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510057311.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-25
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

The prior art is difficult to quickly and effectively detect the concentration of metal ions such as iron, chromium and aluminum in water bodies, affecting the timely treatment of polluted water bodies.

Method used

A zinc complex crystal material is synthesized with metal zinc using fluorenyl carboxylic acid ligand and pyridine ligand. This material achieves rapid detection of iron, chromium, and aluminum ions through fluorescence emission spectroscopy.

Benefits of technology

The zinc complex crystal material can efficiently and quickly detect Cr3+, Al3+ and Fe3+ ions, exhibit high sensitivity and selective response, and has a wide range of application prospects as fluorescence detection materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875134A_ABST
    Figure CN119875134A_ABST
Patent Text Reader

Abstract

The invention discloses a zinc complex crystal material for fluorescence detection of metal ions as well as a preparation method and application of the zinc complex crystal material. Specifically, the crystal belongs to a triclinic system, the space group is # imgabs 0 #, the molecular formula is C72H56N2O8Zn2, the molecular weight is 1207.92, and the cell parameters are as follows: # imgabs 1 # alpha is equal to 70.7410 (10) degrees, beta is equal to 84.2950 (10) degrees, and gamma is equal to 68.2890 (10) degrees; the prepared material has a clear space structure and an accurate molecular formula, can efficiently and rapidly detect Cr < 3 + >, Al < 3 + > and Fe < 3 + > ions, and has a wide application prospect as a fluorescence sensor. The technology has the advantages of simplicity in operation, low cost, stable performance and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of crystal material chemistry, and in particular relates to a zinc complex crystal material for fluorescent detection of metal ions and a preparation method and application thereof. Background Art

[0002] Metal coordination compound crystal materials, referred to as metal complex crystal materials, are also commonly called Metal-Organic Frameworks (MOFs), which are organic-inorganic hybrid materials that form intramolecular pores through the self-assembly of organic ligands and metal ions or clusters through coordination bonds. MOFs materials have been widely used in gas adsorption separation, catalysis, ion detection and other fields. In human life, traces of heavy metals are everywhere. Although some heavy metal elements such as iron, chromium, and manganese are trace elements necessary for life activities, like most other heavy metal elements that are necessary for non-living things, when their content in the body exceeds a certain concentration, they will cause great harm to the body. Therefore, the detection of metal ions in water bodies is of great significance for the timely treatment of polluted water bodies.

[0003] MOFs fluorescent probe is a special type of sensor that has attracted attention in the field of analytical sensing and optical imaging due to its high sensitivity, fast response time and simple technology. And the fluorescence-based compounds have strong electronic conjugation, which means large electron delocalization and high fluorescence efficiency. In recent years, anthraquinones, pyrene derivatives, biphenyls, styrenes, imidazoles and polyurethanes have become the main raw materials for fluorescent probes. Among them, fluorene is a rigid plane composed of a five-membered ring connecting two benzene rings, and is a fluorescent group with strong fluorescence. Their derivatives have unique roles in photoluminescent and electroluminescent materials due to the physical properties of the biphenyl unit. Summary of the invention

[0004] The present invention aims at the problems existing in the prior art and provides a zinc complex crystal material for fluorescent detection of metal ions and a preparation method and use thereof. The present invention synthesizes a zinc complex crystal material by using fluorenyl carboxylic acid ligands and pyridine ligands with metal zinc, and can realize rapid detection of iron, chromium and aluminum ions by using fluorescence emission spectrum.

[0005] The technical solution adopted by the present invention to solve the above technical problems is: the composition structure formula of the zinc complex crystal material is [Zn2(L)2(L1)] n (L=3,3'-(9,9-diethyl-9H-fluorene-2,7-diyl)dibenzoic acid, L1=4,4'-bipyridine), the crystal belongs to the triclinic system, the space group is The molecular formula is C 72 H 56 N2O8Zn2, molecular weight is 1207.92, unit cell parameters α=70.7410(10)°, β=84.2950(10)°, γ=68.2890(10)°; Figure 1 The results show that the asymmetric structural unit of the crystalline material includes a Zn(II) ion, an L ligand and an L1 ligand with an occupancy of 0.5; the Zn(II) ion adopts a hexacoordinated octahedral configuration, four oxygen atoms come from the carboxyl group of the ligand L, one nitrogen atom comes from the pyridinic nitrogen of the ligand L1, and the other position is occupied by Zn–Zn, with a distance of ( Figure 2 ), Figure 2 For clarity, hydrogen atoms are ignored; the coordination structural unit is bridged by ligands L and L1 to form a two-dimensional layered structure ( Figure 3 ), Figure 3 For clarity, hydrogen atoms are ignored; the two-dimensional structure is formed by intermolecular forces, CH…O and π…π action (the distance between adjacent surfaces is ), forming a three-dimensional network structure ( Figure 4 ), Figure 4 Hydrogen atoms are ignored for clarity.

[0006] The present invention also provides a method for preparing the crystalline material, which comprises the following steps:

[0007] Weigh a certain amount of ligand L, ligand L1 and zinc salt into a glass bottle, and dissolve them in a mixed solution consisting of N,N-dimethylformamide (DMF), anhydrous ethanol and distilled water; heat the vial containing the mixed solution at 75-95° C. for 48-72 hours, and then cool it to room temperature to obtain yellow block crystals, which are the zinc complex crystal material.

[0008] The zinc salt is zinc nitrate hexahydrate;

[0009] The molar ratio of the ligand L, L1 and zinc salt is 1:1:2;

[0010] The ligand L, whose English name is 3,3'-(9,9-diethyl-9H-fluorene-2,7-diyl)dibenzoic acid, has a molecular formula of C 31 H 26 O4, molecular weight is 462.55, and its structural formula is shown in formula (I):

[0011]

[0012] The ligand L1, whose English name is 4,4'-bipyridine, has a molecular formula of C 10 H8N2, with a molecular weight of 156.18, has a simplified structural formula as shown in formula (II):

[0013]

[0014] All substances or solvents involved in the reaction are chemically pure.

[0015] The present invention also provides the use of the zinc complex crystal material, which can be used as a material for fluorescent detection of metal ions and can efficiently and quickly detect Cr 3+ 、Al 3+ and Fe 3+ ions, and the zinc complex crystal material has broad application prospects as a fluorescent sensor.

[0016] Compared with the prior art, the present invention is characterized in that:

[0017] The zinc complex crystal material was synthesized by a solvothermal method through a mixed ligand method. The fluorescence emission properties of the material were 3+ 、Al 3+ and Fe 3+ The trivalent metal ions showed high sensitivity and selective response, especially in Cr 3+ 、Al 3+ and Fe 3+ In the presence of these ions the crystalline material exhibits a specific fluorescent "on" response.

[0018] The ligands L and L1 used in the present invention have a specific conjugated π system and a unique spatial structure. The two-dimensional and three-dimensional structures formed have a specific spatial structure; the two-dimensional layers have specific intermolecular forces, specific hydrogen bonds and CH…O interactions. and π…π action (the distance between adjacent surfaces is ); the distance between Zn–Zn in the coordination unit is These specific structures and parameters determine that the prepared crystal material has high stability, specific fluorescence properties and unique fluorescence response properties to specific metal ions, making the prepared crystal material have broad application prospects as a fluorescence detection reagent material or as a fluorescence sensor. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is the basic structural unit of the zinc complex crystal material of the present invention;

[0020] Figure 2 is a coordination environment diagram of Zn(II) ions in the zinc complex crystal material of the present invention;

[0021] Figure 3 It is a two-dimensional layered structure of the zinc complex crystal material of the present invention along the b-axis direction;

[0022] Figure 4 The three-dimensional network structure of the zinc complex crystal material of the present invention along the c-axis direction;

[0023] Figure 5 Thermogravimetric spectrum of the zinc complex crystal material of the present invention;

[0024] Figure 6 It is a fluorescence response diagram of the zinc complex crystal material suspension of the present invention to the presence of different metal ions;

[0025] Figure 7 This is a test diagram of the anti-interference performance of the zinc complex crystal material of the present invention. Figure 7 (a) is the histogram of the fluorescence detection ions of the crystal material suspension. Figure 7 (b) Comparison of the fluorescence intensity of the crystal under the interference of different metal ions when Al(III) ions are present and absent. The probe in the figure is a crystal material suspension and the interfering ion is K + ,Na + ,Ag + ,Co 2+ ,Ba 2 + ,Cu 2+ ,Ni 2+ ,Zn 2+ ,Cd 2+ Mg 2+ ,Pb 2+ ,Cr 3+ ,Fe 3+ , Figure 7 (c) Comparison of fluorescence intensity of crystal material suspension under different metal ion interference when Cr(III) ions are present and absent. In the figure, the probe is the crystal suspension and the interfering ion is K + ,Na + ,Ag + ,Co 2+ ,Ba 2+ ,Cu 2+ ,Ni 2+ ,Zn 2+ ,Cd 2+ Mg 2+ ,Pb 2+ ,Al 3+ ,Fe 3+ , Figure 7 (d) Comparison of fluorescence intensity of crystal material suspension under different metal ion interference in the presence and absence of Fe(III) ions. The probe in the figure is zinc complex crystal suspension, and the interfering ion is K+ ,Na + ,Ag + ,Co 2+ ,Ba 2+ ,Cu 2+ ,Ni 2+ ,Zn 2+ ,Cd 2+ Mg 2+ ,Pb 2+ ,Cr 3+ ,Al 3+ ;

[0026] Figure 8 This is a sensitivity test diagram of the zinc complex crystal of the present invention. Figure 8 (a) The fluorescence spectra of the crystal material suspension in the presence of different concentrations of aluminum ions, Figure 8 (b) Linear fitting curve of the crystal material suspension in the presence of different concentrations of aluminum ions, Figure 8 (c) Fluorescence spectra of the crystal material suspension in the presence of different concentrations of chromium ions. Figure 8 (d) Linear fitting curve of the crystal material suspension in the presence of different concentrations of chromium ions, Figure 8 (e) Fluorescence spectra of the crystal material suspension in the presence of different concentrations of iron ions. Figure 8 (f) Linear fitting curve of the crystal material suspension in the presence of different concentrations of iron ions. DETAILED DESCRIPTION

[0027] The present invention is further described in detail below with reference to the embodiments.

[0028] Embodiment 1:

[0029] Zn(NO3)2·6H2O (5.95 mg, 0.02 mmol), L (4.63 mg, 0.01 mmol), and L1 (1.56 mg, 0.01 mmol) were placed in 5 mL glass bottles and dissolved in a mixed solution of N,N-dimethylformamide (DMF) (1.5 mL), anhydrous ethanol (1 mL), and distilled water (1 mL) in a volume ratio of 1.5:1:1. The vial containing the mixed solution was heated at 90°C for 48 hours and then cooled to room temperature. Yellow block crystals were obtained.

[0030] Embodiment 2:

[0031] Zn(NO3)2·6H2O (11.9 mg, 0.04 mmol), L (9.26 mg, 0.02 mmol), and L1 (3.12 mg, 0.02 mmol) were placed in 5 ml glass bottles and dissolved in a mixed solution consisting of DMF (1.5 mL), anhydrous ethanol (1 mL), and distilled water (1 mL) in a volume ratio of 1.5:1:1. The vial containing the mixed solution was heated at 75°C for 72 hours and then cooled to room temperature. Yellow block crystals were obtained.

[0032] Embodiment 3:

[0033] Zn(NO3)2·6H2O (2.98 mg, 0.01 mmol), L (2.31 mg, 0.005 mmol), and L1 (0.78 mg, 0.005 mmol) were placed in 5 mL glass bottles and dissolved in a mixed solution consisting of DMF (1.5 mL), anhydrous ethanol (1 mL), and distilled water (1 mL) in a volume ratio of 1.5:1:1. The vial containing the mixed solution was heated at 95°C for 60 hours and then cooled to room temperature. Yellow block crystals were obtained.

[0034] The yellow block crystals prepared in Example 1 were subjected to single crystal X-ray diffraction analysis. Crystals of suitable size and regular shape were selected at room temperature and fixed on the test needle with epoxy resin glue. The test needle was then placed on a Rigaku Oxford XtaLAB PRO diffractometer and the graphite monochromated MoKα rays were used. The samples were tested, and the CrysAlisPro-Agilent software was used to collect data, screen diffraction points, determine the lattice type, and perform absorption correction and data restoration. The crystal structure was solved directly by the ShelXS program, and anisotropic refinement was performed using ShelXL. 2 The full matrix least squares method was used for refinement and correction. The coordinates of non-hydrogen atoms in the structure were gradually determined by difference Fourier peak synthesis and anisotropic refinement was performed. Hydrogen atoms were obtained by theoretical hydrogenation. All hydrogen atoms were isotropically refined and a complete Cif file was obtained. In cif, the residual factor R1 value (R_factor_gt) was 0.0349, the multi-diffraction point goodness of fit S or GooF value (goodness_of_fit_ref) was 1.039, and the average drift value (shift / su_mean) of the final refinement process was 0.000. These parameters have very well met the precise data requirements for crystal structure analysis required by crystallography. The results of X-ray single crystal diffraction test analysis showed that the structural formula of the prepared zinc complex crystal material was [Zn2(L)2(L1)] n It belongs to the triclinic system and its space group is The molecular formula is C 72 H 56 N2O8Zn2, molecular weight is 1207.92, unit cell parameters α=70.7410(10)°, β=84.2950(10)°, γ=68.2890(10)°; Figure 1 It is shown that the crystal [Zn2(L)2(L1)] n The asymmetric structural unit of the Zn(II) ion includes a Zn(II) ion, an L ligand, and an L1 ligand with an occupancy of 0.5; the Zn(II) ion adopts a hexacoordinated octahedral configuration, four oxygen atoms come from the carboxyl group of the ligand L, one nitrogen atom comes from the pyridinic nitrogen of the ligand L1, and the other position is occupied by Zn–Zn, with a distance of ( Figure 2 ); The coordination structural unit forms a two-dimensional layered structure through the bridging of ligands L and L1 ( Figure 3 );The two-dimensional structure is affected by intermolecular forces, CH…O and π…π action (the distance between adjacent surfaces is ), forming a three-dimensional network structure ( Figure 4 ). The test results show that the prepared yellow block crystal is the zinc complex crystal material.

[0035] The zinc complex crystal material prepared above was subjected to thermogravimetric analysis ( Figure 5 ), the results showed that the skeleton of the prepared crystal material could remain stable at around 320°C, indicating that the crystal has good thermal stability.

[0036] In order to evaluate the detection effect of the prepared crystal material on metal ions in water, 3.9 mg of the prepared crystal material was dissolved in deionized water to prepare a suspension of the crystal material with a concentration of 100 μM. Subsequently, 200 μL of different metal ion nitrate solutions (metal ions are K + ,Na + ,Ag + ,Co 2+ ,Ba 2+ ,Cu 2+ ,Ni 2+ ,Zn 2+ ,Cd 2+ Mg 2+ ,Pb 2+ ,Cr 3+ ,Al 3+ ,Fe 3+ ; The concentration of each metal ion is 10 -4 M) was added to 1800 μL of the suspension of the crystal material, and then the fluorescence spectrum analysis test was performed and the fluorescence spectrum was recorded. The results showed that when Cr3+ 、Al 3+ or Fe 3+ ions, the fluorescence intensity of the test was significantly enhanced, and the fluorescence intensity increased by about 9.5 times, 8.7 times and 7.2 times, respectively, indicating that the prepared crystal material has good 3+ 、Al 3+ or Fe 3+ Ions have specific response properties ( Figure 6 ).

[0037] Anti-interference test( Figure 7 ). In a real water environment, taking tap water as an example, multiple metal ions coexist, and an anti-interference test experiment is carried out to evaluate the detection performance of the prepared crystal material for metal ions. The interfering ion is K + ,Na + ,Ag + ,Co 2+ ,Ba 2+ ,Cu 2+ ,Ni 2+ ,Zn 2+ ,Cd 2+ Mg 2+ ,Pb 2+ In the absence of interfering ions, the prepared crystal material has a strong affinity for the test ion Cr 3+ 、Al 3+ and Fe 3+ The fluorescence intensity response of ions is significantly enhanced ( Figure 7 a in the above). Each test ion (Cr 3+ , Al 3+ and Fe 3+ ) were tested for fluorescence spectra in the presence of 13 interfering ions other than themselves ( Figure 7 b- Figure 7 d). The test results show that in the presence of interfering ions, the test ion Cr 3+ 、Al 3+ or Fe 3+ The fluorescence intensity enhancement is still significant. The above test results show that the prepared crystal material has good fluorescence performance under complex environment. 3+ 、Al 3+ and Fe 3+ Ions have good selective recognition and detection, and they have broad application prospects as ion detection sensors.

[0038] Sensitivity test( Figure 8 ). Since the prepared crystal material has a strong affinity for Cr 3+ 、Al 3+ and Fe 3+ions have obvious recognition and detection performance, and the zinc complex crystal material was analyzed and tested using quantitative fluorescence titration to evaluate the test sensitivity of the zinc complex crystal material as a sensor. 3+ 、Al 3+ or Fe 3+ As the ion concentration increases, the fluorescence increases significantly. Within a certain concentration range, the fluorescence intensity shows a good linear relationship with the ion concentration. The Al 3+ The detection limit of Fe 3+ The detection limit of Cr 3+ The detection limit was 0.19 μM.

Claims

1. A zinc complex crystal material for fluorescent detection of metal ions, characterized in that: The composition structure of the zinc complex crystal material is [Zn2(L)2(L1)] n ; The crystal belongs to the triclinic system, and the space group is The molecular formula is C 72 H 56 N2O8Zn2, molecular weight is 1207.92, unit cell parameters α=70.7410(10)°,β=84.2950(10)°,γ=68.2890(10)°;The asymmetric structural unit of the crystalline material includes a Zn(II) ion, an L ligand and an L1 ligand with an occupancy of 0.5;The Zn(II) ion adopts a hexacoordinated octahedral configuration, four oxygen atoms come from the carboxyl group of the ligand L, one nitrogen atom comes from the pyridinic nitrogen of the ligand L1, and the other position is occupied by Zn–Zn, and the distance between Zn–Zn is The coordination structural unit forms a two-dimensional layered structure through the bridging of ligands L and L1; the two-dimensional structure is connected by intermolecular forces, CH…O and π…π action (the distance between adjacent surfaces is ), forming a three-dimensional network structure; The structural formula is [Zn2(L)2(L1)] n The ligand L in the middle is 3,3'-(9,9-diethyl-9H-fluorene-2,7-diyl)dibenzoic acid, and its molecular formula is C 31 H 26 O4, molecular weight is 462.55, and its structural formula is shown in formula (I): The structural formula is [Zn2(L)2(L1)] n The middle ligand L1, whose English name is 4,4'-bipyridine, has a molecular formula of C 10 H8N2, molecular weight is 156.18, and its structural formula is shown in formula (II):

2. A method for preparing a zinc complex crystal material for fluorescent detection of metal ions as claimed in claim 1, characterized in that: The preparation method comprises the following steps: Weigh a certain amount of ligand L, ligand L1 and zinc salt into a glass bottle, dissolve them in a mixed solution of DMF, anhydrous ethanol and distilled water, heat the vial containing the mixed solution at 75-95° C. for 48-72 hours, and then cool to room temperature to obtain yellow block crystals, which are the zinc complex crystal materials; The zinc salt is zinc nitrate hexahydrate; The molar ratio of the ligands L, L1 and the zinc salt is 1:1:

2.

3. Use of the zinc complex crystal material according to claim 1 or the zinc complex crystal material prepared by the preparation method of the zinc complex crystal material according to claim 2, characterized in that: The zinc complex crystal material is used as a material for fluorescent detection of metal ions in detecting Cr 3+ 、Al 3+ and Fe 3+ The zinc complex crystal material has application as a fluorescent sensor.

Citation Information

Patent Citations

  • Metal catalyst based on metal-organic framework as well as preparation method and application thereof

    CN101596465A

  • Zinc complex semiconductor crystal material and preparation method and application thereof

    CN116288730A

  • Multi-Functional Copolymers Comprising Rare Earth Metal Complexes and Devices Thereof

    US20070290199A1